Noninvasive Ventilation in Treatment of Respiratory Failure-Related COVID-19 Infection: Review of the Literature - Bushra Mina; Alexander Newton; Vijay Hadda (Canadian Respiratory Journal)
The recently diagnosed coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in December 2019 commonly affects the respiratory system. The incidence of acute hypoxic respiratory failure varied among epidemiological studies with high percentage of patients requiring mechanical ventilation with a high mortality. Noninvasive ventilation is an alternative tool for ventilatory support instead of invasive mechanical ventilation, especially with scarce resources and intensive care beds. Initially, there were concerns by the national societies regarding utilization of noninvasive ventilation in acute respiratory failure. Recent publications reflect the gained experience with the safe utilization of noninvasive mechanical ventilation. Noninvasive ventilation has beneficiary role in treatment of acute hypoxic respiratory failure with proper indications, setting, monitoring, and timely escalation of therapy. Patients should be monitored frequently for signs of improvement or deterioration in the clinical status. Awareness of indications, contraindications, and parameters reflecting either success or failure of noninvasive ventilation in the management of acute respiratory failure secondary to COVID-19 is essential for improvement of outcomes.